The school as anenvironmentofciviceducation: an approach fromtheScientificLiteracyandTechnological (Research, Society and Development, 2017)
This is a reflection carried out with the objective of understanding the role of the school in the citizen training of its students, based on the approach of the Scientific and Technological Literacy. The reflections guided themselves by means of historical understanding and concepts of Scientific Literacy and Technology in the school context, in addition to seeking to understand the development of the “to be” teacher and student in this important process of change, as well as ascertain the mains kills employed for civic education in the school environment by the middle of this perspective. It was found that the incentive of the sections combined with others kills inherent in the process facilitates the development of autonomy of individuals, making the mable to build their knowledge, integrated the needs of the community, contributing to civic education.